Optimization of Flux Switching Generator Using Sequential Technique - Murugan, Lishaallani; Sulaiman, Erwan (Evolution in Electrical and Electronic Engineering, 2024)
This study describes the optimization of flux switching generator (FSG) using a technique called sequential technique. Several FSG designs have been observed and studied before fixing for one specific design of the generator. However, all the designs encountered a common drawback of having high voltage drop and low output voltage. Thus, this study had outlined to serve the purpose of designing FSG with the maximum output voltage. The basic design of FSG used in this project was done using the JMAG software. This generator was designed based on specific parameters fixed which are the stator with 42.5mm of diameter, rotor with 25.5mm diameter, permanent magnet with 6mm width, and stack length of 30mm was used. Upon successful optimization, the design becomes the initial design for the project. The initial design was analyzed as a no-load test to obtain the results of coil-flux linkage, maximum back EMF, maximum output fundamental voltage and maximum apparent power delivered by the generator. All the results were then analyzed and explained in this paper. In addition, a study of six different sequences in designing the FSG were conducted in this study which plays around the three basic components of FSG which are stator, rotor and permanent magnet. The parameters of all the components were modified to the sequences decided, which will come up with different values of fundamental output voltage before deciding the best sequence by observing the output voltage of each of the sequences.